Comparative Anatomical Study of thyroid gland in adult indigenous gazelle (Gazella subgutturosa) and sheep - Iman Khaleel; Ali Salih (Kufa Journal for Veterinary Medical Sciences, 2017)
The present work was carried out on 12 adult healthy indigenous gazelle and sheep (6 gazelle and 6 sheep) to study the anatomical features of thyroid gland in these two animals and to compare between them. The present findings showed that the thyroid gland in both species was made up of two reddish- brown bi-lobed structure (right and left lobes) connected by a thin tissue ; an isthmus, they were asymmetrically located on the cranial portion on the lateral side of the trachea in gazelle, while in sheep they located ventrolaterally. The isthmus connect the right and left lobes from there caudal extremity in gazelle while in sheep from there caudal ends about 5 mm and it cross the ventral aspect of the trachea about 7th – 8th tracheal ring level in gazelle, whereas in sheep at 4th tracheal ring. The anatomical data revealed no significant important in the weight of the gland between gazelle and sheep, and between left and right lobe in both gazelle and sheep in weight, dimensions and volume, but significantly importance between gazelle and sheep in the length, width and volume of isthmus at p<0.05 and in the length of the right and left lobe and only thickness of the right lobe between gazelle and sheep at p<0.05. thyroid gland was supplied by the cranial and caudal thyroid arteries in gazelle, while in sheep through the dorsal and ventral thyroidal arteries, all arteries were originate from the common carotid artery . Keyword: Gazelle, Thyroid gland, Isthmus, Right lobe, left lobe, Thyroid artery.